2019
DOI: 10.3390/md17090485
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Effect of Triglyceride Accumulation by Large Yellow Croaker Roe DHA-PC in HepG2 Cells

Abstract: The phospholipids (PLs) of large yellow croaker (Pseudosciaena crocea, P. crocea) roe contain a high level of polyunsaturated fatty acids, especially docosahexaenoic acid (DHA), which can lower blood lipid levels. In previous research, PLs of P. crocea roe were found able to regulate the accumulation of triglycerides. However, none of these involve the function of DHA-containing phosphatidylcholine (DHA-PC), which is the main component of PLs derived from P. crocea roe. The function by which DHA-PC from P. cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…7): (1) enhancing PPARγ activity, subsequently down-regulating the TLR-4/NF-κB and c-Jun N-terminal kinase (JNK) pathways, resulting in inhibiting the synthesis and release of inflammatory factors, such as IL-1β and TNF-α; 37,39 (2) reducing serum and hepatic free fatty acid levels by suppressing hepatic SREBP-1c mediated lipogenesis and increasing carnitine palmitoyl transferase 1a and acyl-CoA oxidase 1 expression levels; 40 and (3) promoting fatty acid β-oxidation mediated by PPARα in liver and alleviating lipid peroxidation. 36 We could not find any reference to test the biological properties of PC (16:1/22:6) by searching PubMed, Lipid Maps and PubChem. Our hypothesis could be tested by administration of pure PC species including PC (16:1/22:6) and PC (16:0/22:6) for a comparison group, in various animal models of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7): (1) enhancing PPARγ activity, subsequently down-regulating the TLR-4/NF-κB and c-Jun N-terminal kinase (JNK) pathways, resulting in inhibiting the synthesis and release of inflammatory factors, such as IL-1β and TNF-α; 37,39 (2) reducing serum and hepatic free fatty acid levels by suppressing hepatic SREBP-1c mediated lipogenesis and increasing carnitine palmitoyl transferase 1a and acyl-CoA oxidase 1 expression levels; 40 and (3) promoting fatty acid β-oxidation mediated by PPARα in liver and alleviating lipid peroxidation. 36 We could not find any reference to test the biological properties of PC (16:1/22:6) by searching PubMed, Lipid Maps and PubChem. Our hypothesis could be tested by administration of pure PC species including PC (16:1/22:6) and PC (16:0/22:6) for a comparison group, in various animal models of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…11 Numerous studies have indicated that DHA-enriched PC plays a vital role in improving lipid metabolism and alleviating hepatic steatosis, contributing to insulin resistance improvement, hepatic TAG synthesis attenuation and fatty acid β-oxidation enhancement. [35][36][37] Meanwhile, it has been demonstrated that DHA-enriched PC could reduce the elevated levels of serum inflammatory factors in vivo and vitro experiments. 38 Hence, we proposed a hypothesis that PC (16:1/22:6) might exert beneficial and unique effects on hepatic function, lipid metabolism and inflammation, since this lipid species had the highest or second highest VIP scores following FO + D or FO interventions, respectively.…”
Section: Papermentioning
confidence: 99%
“…In China, large yellow croaker ( Larimichthys Crocea ) roe is a kind of major byproduct containing a high amount of DHA-PLs [ 40 ]. LYCRPLs have great nutritional value [ 41 ], and their inhibitory effect on the accumulation of triglycerides was studied at the cellular level [ 42 ] in our early research. Previous animal experiments have also shown that LYCRPLs can significantly regulate lipid metabolism and improve the intestine microbiota disorder induced by a high-fat diet [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies, LYCR is not only a source of high-quality protein but also rich in C20:5n3 (eicosapentaenoic acid, EPA) and C22:6n3 (docosahexaenoic acid, DHA), which are beneficial to lipid metabolism . Based on what we know, current research on LYCR mainly focused on LYCR phospholipids, LYCR isolated proteins, LYCR oil, and LYCR hydrolysates . However, the development of fish roe products of LYCR is still necessary.…”
Section: Introductionmentioning
confidence: 99%